EumicrobeDBLite: a lightweight genomic resource and analytic platform for draft oomycete genomes. (3rd January 2017) - Panda, Arijit; Sen, Diya; Ghosh, Arup; Gupta, Akash; C., Mathu Malar; Prakash Mishra, Gyan; Singh, Deeksha; Ye, Wenwu; Tyler, Brett M.; Tripathy, Sucheta
Summary: We have developed EumicrobeDBLite—a lightweight comprehensive genome resource and sequence analysis platform for oomycete organisms. EumicrobeDBLite is a successor of the VBI Microbial Database (VMD) that was built using the Genome Unified Schema (GUS). In this version, GUS has been greatly simplified with the removal of many obsolete modules and the redesign of others to incorporate contemporary data. Several dependences, such as perl object layers used for data loading in VMD, have been replaced with independent lightweight scripts. EumicrobeDBLite now runs on a powerful annotation engine developed at our laboratory, called 'Genome Annotator Lite'. Currently, this database has 26 publicly available genomes and 10 expressed sequence tag (EST) datasets of oomycete organisms. The browser page has dynamic tracks presenting comparative genomics analyses, coding and non‐coding data, tRNA genes, repeats and EST alignments. In addition, we have defined 44 777 core conserved proteins from 12 oomycete organisms which form 2974 clusters. Synteny viewing is enabled by the incorporation of the Genome Synteny Viewer (GSV) tool. The user interface has undergone major changes for ease of browsing. Queryable comparative genomics information, conserved orthologous genes and pathways are among the new key features updated in this database. The browser has been upgraded to enable user upload of GFF files for quick view of genome annotation comparisons. The toolkit page integrates the EMBOSS package and has a gene prediction tool. Annotations for the organisms are updated once every 6 months to ensure quality. The database resource is available atwww.eumicrobedb.org .